Simulation Of The Queue For Collecting Village Social Assistance Funds Using The Exponential Method - Triana Dewi lestari; Akim m h pardede; katen lumbanbatu (Yayasan Kita Menulis, 2023)
Abstract This research aims to model and analyze the queuing process for collecting Village Bansus funds using an exponential distribution-based simulation method. The exponential method is used to describe the time variability between the arrival of the applicant and the service time in the queue. By utilizing simulation software, this research will examine various fund collection scenarios, including the effect of the number of service personnel on applicant waiting times and the efficiency of the fund collection process. It is hoped that the results of this simulation can provide recommendations for increasing efficiency in the process of collecting Village Bansus funds, including determining the optimal number of service officers. Apart from that, this research can also help village governments in planning and managing the Village Assistance program so that it can be more effective and responsive to community needs. This simulation provides important insight into how the queuing process can be optimized to improve the quality of service to applicants for Village Bansus funds.